2014
DOI: 10.1002/jbmr.2206
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of Chondroadherin: A New Regulator of Osteoclast Motility Counteracting Bone Loss

Abstract: Chondroadherin (CHAD) is a leucine-rich protein promoting cell attachment through binding to integrin a 2 b 1 and syndecans. We observed that CHAD mRNA and protein were lower in bone biopsies of 50-year-old to 65-year-old osteoporotic women and in bone samples of ovariectomized mice versus gender/age-matched controls, suggesting a role in bone metabolism. By the means of an internal cyclic peptide (cyclicCHAD), we observed that its integrin binding sequence impaired preosteoclast migration through a nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…The genes ALP, ON, CHAD, SP7, and Sox9 had a higher expression with respect to cells t h a tw e r eg r o w no nt h ep l a s t i cv e s s e l( T C P S )a td3 postseeding. Cells that were grown on scaffold displayed higher expression levels of mRNAs of ALP, CHAD, SP7,andSOX9 genes than did those that were grown in the presence of OM at d 3 postseeding (29)(30)(31)(32)(33). Three genes-OCN, CHAD,andSox9-had a higher expression with respect to cells that were grownontheplasticvessel(TCPS),witha2-2.5 log 2 fold increase at d 9 postseeding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The genes ALP, ON, CHAD, SP7, and Sox9 had a higher expression with respect to cells t h a tw e r eg r o w no nt h ep l a s t i cv e s s e l( T C P S )a td3 postseeding. Cells that were grown on scaffold displayed higher expression levels of mRNAs of ALP, CHAD, SP7,andSOX9 genes than did those that were grown in the presence of OM at d 3 postseeding (29)(30)(31)(32)(33). Three genes-OCN, CHAD,andSox9-had a higher expression with respect to cells that were grownontheplasticvessel(TCPS),witha2-2.5 log 2 fold increase at d 9 postseeding.…”
Section: Discussionmentioning
confidence: 98%
“…4A). Of interest, the scaffold induced osteogenic gene markers, such as ALP, CHAD, ON, and transcription factors SP7 and SOX9 with respect to control at d 3 (29)(30)(31)(32)(33). The biomaterial continued to produce its osteogenic effect at d 9.…”
Section: Osteogenic Markersmentioning
confidence: 96%
“…The structural information on the C-terminal domain presented here can now be used to improve existing therapeutic peptides. For example, the cyclic peptide 306-326 investigated by Capulli et al (2014) is based on the idea that the peptide will cyclize through the originally proposed disulfide-bonding pattern Cys306-Cys326 (Neame et al, 1994), whereas the true disulfide is between Cys304 and Cys326. Cys306 is 14 Å from Cys326, which may distort the peptide conformation in solution.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in the mRNA level of CHAD by MK-4 treatment were not consistently observed within 48 h, whereas strong expression of its protein was clearly visible by immunocytochemistry. CHAD has been reported to reduce preosteoclast motility and bone resorption without affecting osteoblast parameters, including the expression of runt related transcription factor 2 and BGLAP, the activity of ALP and bone formation (30). Therefore, the findings of the current study indicated a beneficial effect on bone formation in response to genistein + MK-4 treatment.…”
Section: ------------------------------------------------------------mentioning
confidence: 48%